Autosomal dominant retinitis pigmentosa mapping to chromosome 7p exhibits variable expression. Issue 1 (January 1995) - Kim, R Y; Fitzke, F W; Moore, A T; Jay, M; Inglehearn, C; Arden, G B; Bhattacharya, S S; Bird, A C
Abstract : The genetic locus causing autosomal dominant retinitis pigmentosa (adRP) has recently been mapped in a large English family to chromosome 7p. Eight affected members of this family were studied electrophysiologically and psychophysically with dark adapted static threshold perimetry and dark adaptometry. The phenotypes observed fell into three categories: minimally affected with no symptoms, and normal (or near normal) electrophysiology and psychophysics; moderately affected with mild symptoms, abnormal electroretinograms, and equal loss of rod and cone function in affected areas of the retina; and severely affected with extinguished electroretinograms and barely detectable dark adapted static threshold sensitivities. The mutation in the gene on 7p causing adRP in this family causes regional retinal dysfunction with greatly variable expressivity ranging from normal to profoundly abnormal in a manner not explained by age.